Early growth and survival of Avicennia alba seedlings under excessive sedimentation - Affandi, N.A.M.; Kamali, B.; Mz, R.; Tamin, N.M.; Hashim, Roslan (2010)
A field study of growth and survival of Avicennia alba seedlings was conducted at a reforestation site where excessive sediment accretion resulted in seedling burial. A nearby natural habitat, where the sedimentation was not active, was also monitored as control plot. Seedlings height and number of leaves increments and survival rates have been measured monthly as indicators of the growth performance. Seedlings at both sites have similarly produced 2 leaves per month while seedlings at the reforestation site showed a significantly higher stem elongation compared to those in the natural habitat. Higher stem elongation rate in the reforestation site could be attributed to exposure to higher level of sunlight. There was a significant difference between seedlings survival in the natural habitat and the reforestation site (P < 0.05), with 91.66 and 6.82 of the original 314 transplanted and 80 natural seedlings remaining, respectively. We postulate that more than 7 cm sediment burial could significantly increase the mortality of A. alba seedlings (P < 0.05). The results suggest that A. alba may not be suitable for rehabilitation projects in areas subject to high sedimentation.